Pilihan Rasional Petani Padi Miskin di Kabupaten Ngawi Pada Musim Paceklik - Sukma, Panggih Setyaning; Handoyo, Pambudi; Agustin, Dewien (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This research analyzes the rational choices of impoverished rice farmers in Ngawi Regency during paceklik, a critical period with no income from harvests. Using qualitative methods and James Coleman's Rational Choice Theory, this study identifies the farmers' strategies in extreme limitations. Farmers are proven to be rational actors who prioritize survival, manifested in: 1) tight spending control and personal food reserves; 2) seeking supplementary work; 3) taking on